Słowiańska frazeologia gwarowa II (Wydawnictwo Księgarnia Akademicka, 2020)
LINGUISTIC AND CULTURAL IMAGE OF WEEDS PRESERVED IN THE POLISH DIALECTAL PHRASEMES This paper is intended to show and analyze Polish dialectal phrasemes with weeds. The purpose of this study was to investigate linguistic and cultural image of them. Data were excerpt from Kartoteka Słownika gwar polskich, sets of proverbs and dialectal dictionaries. The authoress analyzed phrases with three species of weeds: thistle, cockle and nettle. In folk beliefs the weeds protected against. They were used to health protection. Despite of them weeds are of low value, because they were a threat to other plants that were of high value (mainly grain). The weeds were hard to pull out, grew by themselves (in folk beliefs the creator of them is the devil), so the farmer must work harder. The phrases with weeds describe the negative traits of human (laziness, rudeness) and the human axiology system.